The Mediating Impact of Destination Image on the Association between Influencer-Generated Content and Travel Intentions in Post-Pandemic Tourism - Ahmed, Rizwan (JELAJAH: Journal of Tourism and Hospitality, 2025)
In the case of COVID-19, the intention of people to travel has been influenced heavily by digital touchpoints especially from influencer content. This study aims to explain the mediating role of the image of the destination in the relationship between influencer-generated content and travel intention in the context of tourism recovery following the pandemic. A questionnaire was given to potential travelers, out of a total of 300 administered surveys, 227 responses were considered valid. The relationships were tested using regression analysis. The results of the study suggest that influencer marketing enhances the intention to travel more than anticipated and that the image of the destination as a powerful intermediary factor plays a great role. Travelers who were able exposed to engaging, authentic, and trustworthy content written by travel influencers tended to have high perceptions of the destination. These findings propose integrated digital storytelling and image strategy are necessary for tourism destinations trying to restore confidence and demand in the market. This study adds to the body of literature on digital tourism by providing empirical evidence regarding the mechanisms of travel intention towards tourism destinations in the post-pandemic world.